ANALYSIS OF RESEARCH DEVELOPMENT OF THEORIES OF STATE REGULATION OF MODERN WORLD ECONOMIES - Chub, Anton (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article proves that government regulation in different countries over the past decades, as a rule, is based on modern developments in the framework of economic theories that have dominated in different years. It is emphasized that one of the reasons why no country in the world has so far failed to achieve permanent growth in living standards and avoid crises in various spheres of socio-economic development is the openness of national economies, free capital and large-scale globalization of business. It is determined that such a situation leads, firstly, to general interdependence and rapid spread of crisis phenomena from one state to another. Secondly, with the increase in the number of environmental factors that must be taken into account in the implementation of public administration, the level of uncertainty and economic risks increases. That is why the urgent scientific task is to analyze the experience of applying the systems of state regulation of world economies. The aim of the work is to study and analyze the experience of state regulation in the world, highlighting and substantiating the main economic theories on the basis of which you can justify the formation of regulatory policy. It was found that the role of the state and public administration in economic development has recently intensified scientific thought, and forced to rethink the reasons for the evolution of both economic and managerial functions of the modern state, and their relationship. It is proved that research is needed to identify general trends in changes in the place and role of the state in the economic system. It is also necessary to find out how these historical changes will be able to affect the current processes in Ukraine's economic development. The scientific novelty of this work is the further development of the methodology of state regulation of the economy on the basis of consideration and analysis of basic economic theories. It was proposed to further study the genesis of modern scientific thought, in this regard, in time, while comparing economic theories with a detailed consideration of economic theories transformation stages of state regulation and their basic scientific principles.